Genetic variability, evaluation and characterization of sunflower (Helianthus annuus L.) germplasm (Bangladesh Journal of Botany, 2019)
Fifty accessions of sunflower germplasm were characterized and evaluated for seed yield and its components traits to study the variability present among different germplasm lines. Significant amount of genetic variability was observed for all the characters under study. Seed yield and hull content were identified for highest genotypic (27.08 and 20.14%, respectively) and phenotypic coefficients of variation (27.89 and 20.64%, respectively) and also for high heritability (97.46 and 97.28%, respectively) coupled with high genetic advance (52.19 and 40.49%, respectively) over mean followed by duration of reproductive phase, oil content, 100-seed weight and plant height. Qualitative traits also showed wide variation among the accessions. Majority of the accessions were early in flowering, medium in maturity and medium in head diameter. Among all the accessions, ten lines were observed with short height and ten lines showed high oil content (> 40%). Maximum genetic distance was observed between the accessions EC-601800 and EC- 512687 and utilization of these accessions has been advocated in breeding programme. The results of the present study can be useful for the formation of data base and reference lines, genotype identification and will also be helpful in amplification of future sunflower improvement programme.